HIV prevention intervention for substance users: a review of the literature - Adel Elkbuli; Valerie Polcz; Brianna Dowd; Mark McKenney; Guillermo Prado (BMC, 2019)
Abstract Background Behavioral Interventions are needed to prevent HIV in substance users, which is associated with higher risk for contracting HIV via unprotected sexual intercourse or syringe-based exposure. We reviewed universal HIV prevention interventions targeting intravenous drug users (IDUs) and non-IDUs (NIDUs) to identify which prevention interventions are the most effective at reducing HIV transmission risk among IDU's and NIDU's and identify gaps in the literature. Methods A PubMed literature review (1998-2017), limiting studies to universal HIV prevention interventions targeting adult HIV-negative substance users. Interventions were compared across sample sizes, sociodemographic, intervention setting, study design, use of theoretical models, and intervention effects. Results Of 1455 studies identified, 19 targeted IDUs (n = 9) and NIDUs (n = 10). Both IDU and NIDU studies were conducted in substance use treatment centers and included both group (44% vs. 73%) and individual-based (56% vs. 27%) methods; only one NIDU study used a couple-based intervention. All IDU, and 89% of NIDU, studies used explanatory and behavior-change theoretical models to guide selection of intervention mechanisms. Reduction in frequency of risky sexual behaviors were observed in 33% IDU and 64% NIDU studies, where 56% of IDU studies effectively increased drug use-related hygiene and 67% decreased frequency of injections. Eight studies included start-of-study HIV testing and five examined HIV seroconversion. Conclusion The interventions reviewed demonstrate promising results for decreasing risky sexual practices for NIDUs and reducing high-risk drug practices for IDUs, thereby reducing HIV transmission risk. Future studies should include HIV testing and measurement of HIV seroconversion to fully elucidate intervention effects.